All Days 2012
DOI: 10.2118/157250-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acidizing Sandstone Reservoirs Using HF and Organic Acids

Abstract: Mud acid, which is composed of HCl and HF, is commonly used to remove the formation damage in sandstone reservoirs. However, many problems are associated with HCl, especially at high temperatures.Formic-HF acids have served as an alternative of mud acid for a long period.Several factors may influence the outcome of an acidizing job in sandstone formations.In this research, effects of mineralogy, temperature, and HF concentration were studied.Various clay minerals (kaolinite, chlorite, and illite) were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Carbonic acids are common alternatives to lower the reaction of HCl besides reducing the corrosiveness on well tubulars (Chang et al 2008;Huang et al 2000;Amro 2006; Buijse et al Buijse et al 2004;Yang et al 2012). Despite the efficiency, carbonic acid buffers the pH of organic acid which causes incomplete dissociation of HCl.…”
Section: Carbonate Reservoirs and Matrix Acidizingmentioning
confidence: 99%
“…Carbonic acids are common alternatives to lower the reaction of HCl besides reducing the corrosiveness on well tubulars (Chang et al 2008;Huang et al 2000;Amro 2006; Buijse et al Buijse et al 2004;Yang et al 2012). Despite the efficiency, carbonic acid buffers the pH of organic acid which causes incomplete dissociation of HCl.…”
Section: Carbonate Reservoirs and Matrix Acidizingmentioning
confidence: 99%
“…Nevertheless, the advantages of these chelating agents over HCl were provided such as lower corrosion, not being sensitive to minerals, being stable at high temperature greater than 200 °F and also being biodegradable. Yang et al (2012a) conducted another experiment using a blend of HF-organic acids instead of mud acid to mitigate the problems associated with mud acid. The authors analyzed the kinetic and products of reactions.…”
Section: Retarded Acids and Organic Acidsmentioning
confidence: 99%
“…The authors analyzed the kinetic and products of reactions. The findings of research showed that the type of minerals present in the core plugs has an effect on the reactions (Yang et al 2012b;Yang 2012). Moreover, Zhou and Nasr-El-Din (2013) studied the efficiency of a single-stage sandstone-acid combination, which is a blend of HF and phosphonic acid during sandstone acid stimulation at 300 °F high-temperature formation.…”
Section: Retarded Acids and Organic Acidsmentioning
confidence: 99%
“…A suitable liquid phase system was designed to dissolve it. The mineral phase, which favors the catalytic reaction, was exposed on the surface of the mineral, and a pore structure formed by dissolution and calcination was established on the surface of the mineral [13][14][15][16]. By re-integrating rare earth and transition elements, a solid solution, which is favorable for catalysis, was formed and was more exposed to the surface of the pores, thereby enhancing the dispersibility and acidic sites of the surface active components.…”
Section: Introductionmentioning
confidence: 99%